Buying Decisions on Online Shopping Platforms Influenced by Interesting Marketing Content and E-WOM - Avianti, Widiya Avianti; Adelia Putri (Journal of Management Research and Studies, 2024)
This study aims to analyze the influence of marketing content and E-WOM through the TikTok platform on purchase decisions on Shopee. The source of data in this study was obtained from the results of the distribution of primary questionnaires to student respondents of the STIE Wibawa Karta Raharja management and accounting study program for the 2020-2021 batch, with a research sample of 190 people. The analytical test tool used is SmartPLS 3.0. The results of this study show that marketing content has a significant positive influence (O=0.450) on the construction of purchase decisions. The value of t- statisties in the construct relationship is 9.750. E-WOM through the tiktok platform has a positive and significant influence (O=0.563) on the composition of purchase decisions. The value of t-statisties in this construct relationship is 13.071. Marketing Content and E-WOM through the TikTok platform have a significant effect on Purchase Decisions on shopee.